Anaesthesia of the Malayan sun bears (Helarctos malayanus) using tiletamine-zolazepam-xylazine combination - Che Amat, Azlan; Arshad, Siti Suri; Hassan, Latiffah; Bahaman, Abdul Rani; Mat Naim, R. (Veterinary Association Malaysia, 2010)
Eight Malayan sun bears (Helarctos malayanus) were immobilised with Zoletil® (x = 3.44 mg/kg) and xylazine (x = 0.65 mg/kg). The sun bears were darted intramuscularly by using a blow pipe at muscular areas such as the rump and shoulder regions. Psychological data were recorded every 10 min throughout the immobilisation period. No antagonist drug was used. The drug combination was able to induced smooth, rapid and good anaesthesia with analgesia within 11-30 minutes (mean ± S. D. = 21.1 ± 6.44 min). Time from complete immobilisation to recovery (walking) range from 157 ± 25.6 min (range = 124 – 186 min). No pedal pinch reflex was observed in all animals. The anesthetic depth and analgesia were reasonably adequate to conduct a physical examination and perform minor clinical procedures. There were no significant clinical adverse effects observed except for hypersalivation and frothing during the reversible period.